Ellis Barnes, Amended Charter and Revised Ordinances of the City of Indianapolis 160 (1864) - (:unkn) unknown (My University, 1863)
§ 9: Prohibited discharging a gun or pistol within the city. Violators fined fifty dollars.
Keywords: DISCHARGE